2018
DOI: 10.1016/j.eururo.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Implementation of the European Association of Urology Guidelines Panel Recommendations on Reporting and Grading Complications on Perioperative Outcomes after Robot-assisted Radical Prostatectomy

Abstract: The implementation of the European Association of Urology guidelines on reporting and grading of complications after urologic procedures in prostate cancer patients roughly doubled the complication rate after robot-assisted radical prostatectomy compared to retrospective patient chart review. Moreover, it allowed for the detection of complications after discharge in more than 15% of patients that would have been otherwise missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…In this context, we found that independent predictors of the risk of RAD were seminal vesicle invasion, open approach, and performing ePLND. Moreover, our study confirmed the evidence reported by other studies showing that RARP decreases the risk of hospital readmission after surgery [6,7,28,[30][31][32]34].…”
Section: Overall Association Of Group Factors With the Risk Of Hospitsupporting
confidence: 91%
See 1 more Smart Citation
“…In this context, we found that independent predictors of the risk of RAD were seminal vesicle invasion, open approach, and performing ePLND. Moreover, our study confirmed the evidence reported by other studies showing that RARP decreases the risk of hospital readmission after surgery [6,7,28,[30][31][32]34].…”
Section: Overall Association Of Group Factors With the Risk Of Hospitsupporting
confidence: 91%
“…The incidence of hospital readmission after RP between 30 and 90 days after RP ranges from 3.3 to 9.7%, [6][7][8][28][29][30][31][32][33]. Particularly, readmission rates after ORP range between 5.47 and 10.7% [8,28,29,32,33], and readmission rates after LRP vary between 8.2 and 10.7% [21,22].…”
Section: Overall Association Of Group Factors With the Risk Of Hospitmentioning
confidence: 99%
“…All the 14item criteria of the EAU guidelines were fulfilled [22,23] (Table S1). This is crucial to strengthen our results and avoid underestimating the rate of complications reported [29,30]. Indeed, by fulfilling all the suggested criteria, we ensured the high reliability of the data reported on postoperative complications.…”
Section: Discussionmentioning
confidence: 66%
“…However, these early promising low complication rates may be explained by the fact that the only Brazilian men with nonpalpable lymph nodes without previous DSNB or biopsies were included, which is in contrast to our series of British individuals with a high proportion of palpable nodes and previous DSNBs. Furthermore, complications should be assessed prospectively [25] and definitions of symptomatic lymphocele/seromas, wound infections, and lymphoedema should be developed beforehand.…”
Section: Discussionmentioning
confidence: 99%